Antibody against synthetic peptide of prolactin-inducible protein homologue precursor (PIP-HP) of Bali Cattle (Bos javanicus) saliva as a potential biomarker for immunoassay development (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study aimed to produce and analyze antibody against a synthetic amino acid sequence fragment of PIP-HP of Bali cattle saliva.Materials and Methods: The synthetic amino acid sequence of the PIP-HP (VIRELGICPDDWAVIPIKANRF) was developed, conjugated to bovine serum albumin and was used to immunize Indonesian local rabbits. Positive sera that specific against the PIP-HP were pooled and purified sequentially by implying ammonium sulfate precipitation and protein A affinity methods. Purified antibody was then employed to analyze of PIP-HP in the ruminants’ saliva by means of westernblot assays.Results: A polyclonal antibody specific to asynthetic amino acid sequence fragment of PIP-HP of Bali cattle saliva was successfully produced. Our results show that the antibody potentially to be used to develop an immuno-diagnostic kit. Furthermore, the antibody was also able to inhibit the growth of both Escherichia coli and Staphylococcus aureus cultures significantly (P